Improving Character Development and Learning Achievement of SMPN 3 Cibarusah Students Using PjBL Learning Models On Biotechnology Materials - Wulandari, Wiwin (Lafadz Jaya Publisher, 2022)
Learning Project Based Learning (PjBL) models provide opportunities for teachers to improve nationalist character, mutual cooperation and independent students in learning. The PjBL model gives students the opportunity to experiment with producing work according to related materials. This will make students better understand the learning material and can improve learning achievement. The purpose of the research is to increase the character building and learning achievement by implementing Project Based Learning (PjBL) learning models in biotechnology topics. The research population was students of grade IX-A SMPN 3 Cibarusah academic year 2022/2023 It belonged to class action research. It consists of two cycles. The results of this research showed that the implementation of PjBL was able to increase character building from 68.97% to 89.